Use of Singing Methods to Improve Vocabulary Mastery in Children Aged 5-6 Years - Farichatul Hidayah; Tutuk Zurotun Nasi'ah; Novianti Novianti (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2022)
This study aims to improve vocabulary mastery skills through singing methods using classroom action research. The subjects of this study were students in group B of Dharma Wanita Persatuan II Bangil Kindergarten, Pasuruan, with a total sample of 15 children. Data on children's initial ability in vocabulary mastery are still in the low category, so stimulation is given through singing methods. Based on this, the results of the study obtained showed that there was an increase in the ability to master vocabulary in children with an average score of the ability to distinguish the sounds of letters, words, and the use of sentences in the first cycle in the less category, experiencing an increase in the second cycle in the process of obtaining an average score on excellent criteria. Likewise, the average score of children's ability to express words and sentences clearly in the first cycle, which is in the lower category, has increased in cycle II is also an outstanding category.